2000
DOI: 10.2113/gscanmin.38.3.585
|View full text |Cite
|
Sign up to set email alerts
|

The Pge and Base-Metal Alloys in the Podiform Chromitites of the Luobusa Ophiolite, Southern Tibet

Abstract: PGE and base-metal alloy minerals from podiform chromitites of the Luobusa ophiolite, southern Tibet include Os-Ir, Os-Ir-Ru, Pt-Fe, Ir-Ni-Fe, Fe-Ni-Cr, and Fe-Co with highly variable compositions. Small amounts of diamond, graphite, SiC, an unnamed chromium carbide, iron silicide (Fe-Si), and native Fe, Ni, Cr, Au, Cu and Si also are present. The alloys and native elements were recovered primarily from heavy-mineral separates of the chromitites, but some are included in, or attached to, magnesiochromite grain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 28 publications
4
54
0
2
Order By: Relevance
“…In particular, rocks from Lianping and Leiqiong have low Pt/Rh ratios with strong Pt depletion. A possible explanation for the Pt depletion is that the magmas underwent fractionation of Fe-Pt alloys during an early stage of crystallization of chromite (Bai et al, 2000;Cabri, 1992;Nixon and Hammack, 1991;Peck and Keays, 1990a, b). The early separation of Fe-Pt alloys included in chromites could possibly account for the Pt-depletion in some of Sanshui samples due to the concurrent depletion of Ru.…”
Section: Quantitative Modeling Of Immiscible Sulfide Removalmentioning
confidence: 99%
“…In particular, rocks from Lianping and Leiqiong have low Pt/Rh ratios with strong Pt depletion. A possible explanation for the Pt depletion is that the magmas underwent fractionation of Fe-Pt alloys during an early stage of crystallization of chromite (Bai et al, 2000;Cabri, 1992;Nixon and Hammack, 1991;Peck and Keays, 1990a, b). The early separation of Fe-Pt alloys included in chromites could possibly account for the Pt-depletion in some of Sanshui samples due to the concurrent depletion of Ru.…”
Section: Quantitative Modeling Of Immiscible Sulfide Removalmentioning
confidence: 99%
“…Apart from these UHP minerals as inclusions in chromian spinels, which may be interpreted as UHP xenocrysts accidentally captured by chromian spinel (e.g., Bai et al, 2000;Robinson et al, 2004), Yamamoto et al (2009) found diopsidic clinopyroxene and coesite as exsolution lamellae from chromian spinel. They interpreted the lamella -bearing chromian spinel as a breakdown product from UHP CF (calcium ferrite; CaFe 2 O 4 ) type precursor (chromian spinel), and suggested pressures for formation over 12.5 GPa (> 380 km) (Yamamoto et al, 2009).…”
Section: Ultrahigh-pressure Minerals From Podiform Chromitites: a Reviewmentioning
confidence: 99%
“…A wide variety of unusual minerals, including ultra-high pressure phases such as diamond and coesite, highly reduced minerals such as moissanite, and native elements, carbides, alloys, oxides, sulphides (arsenides) and silicates were found from the podiform chromitites of the Luobusa ophiolite in the Yarlung-Zangbo suture (Yang et al, 2007;Robinson et al, 2004;Bai et al, 2000). Xu et al (this issue) reported thousands of diamond along with over 40 kinds of minerals discovered from the Kangjinla chromitite deposit in the Luobusa ophiolite, providing new key evidence for discussing the origin of the diamond and the hosted chromitite and ophiolite.…”
Section: (Ultra) High-pressure Metamorphic Rocks Ophiolite and Subdumentioning
confidence: 99%
“…These are not only contributed to the knowledge of HPM zones in the Qinghai-Tibet plateau, but also to other places in China and the rest of the world. In turn, these discoveries will have an important impact on the further understanding of the tectonic structure and the characteristic configuration of the Qinghai-Tibet plateau, and the converging dynamic activities between the plates.A wide variety of unusual minerals, including ultra-high pressure phases such as diamond and coesite, highly reduced minerals such as moissanite, and native elements, carbides, alloys, oxides, sulphides (arsenides) and silicates were found from the podiform chromitites of the Luobusa ophiolite in the Yarlung-Zangbo suture (Yang et al, 2007;Robinson et al, 2004;Bai et al, 2000). Xu et al (this issue) reported thousands of diamond along with over 40 kinds of minerals discovered from the Kangjinla chromitite deposit in the Luobusa ophiolite, providing new key evidence for discussing the origin of the diamond and the hosted chromitite and ophiolite.…”
mentioning
confidence: 99%